Kepemimpimanan Profetik Nabi Sulaiman - Qoyyimun Nafal; Kojin Kojin; Ahmad Tanzeh; Imam Fuadi (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to explore the prophetic leadership in the story of the prophet Solomon. First, this story is one of the stories that contains many lessons and can be taken by subsequent leaders with Solomon's firm, clever and disciplined leadership style. Everything is explained in QS. Al-Naml verses 15-44. Second, Prophet Solomon was a prophet and king who did not make wealth a priority even though he had perfect power, but led according to God's rules. Third, the stories in the Qur'an are certainly inseparable from warnings and lessons, so it is necessary for every group to emulate what is taught in the Qur'an, one of which is emulating the leadership attitude of Prophet Solomon. The leadership criteria are: thorough and firm in leading, intellectual, sharp in decisions, virtuous, anti-bribery, physically fit, and always praying.